ANALISIS KESALAHAN SISWA SMP KELAS VIII DALAM MENYELESAIKAN SOAL PEMECAHAN MASALAH MATEMATIS MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL - Metha Puspita Sari Gunawan; Tina Rosyana (IKIP Siliwangi, 2022)
Students who are at the viiith level of junior high school must learn the Two-Variable Linear Equation System (SPLDV). The reason for the study was to see the mistakes of students when working on material problems of the Two-Variable Linear Equation System (SPLDV) using a problem-solving approach. Participants in this study were 32 students of class VIII of SMPN 1 Cililin consisting of 14 men and 18 women. The procedure for the information collection process uses a written exam which is an overview of 5 questions that show problem-solving skills. The data investigation is completed by examining the results of the experiment, then proceeding with drawing conclusions. from this review it can be seen that there are some learners who have misrepresented the question of portrayal of SPLDV material. Based on the studies conducted, there are aspects that trigger students' mistakes in responding to questions, including: 1) Students do not answer questions according to the established strategy. 2) Students are less careful in doing mathematical calculations to complete the theoretical formulations that have been designed and 3) Students do not see the answer again, as a result of which they do not follow a methodical process.